THE USING OF JOURNAL DIALOGUE AND GENRE-BASED APPROACH IN WRITING HORTATORY TEXT A survey at the State Senior High Schools in West Java - Susi Mustika Sari; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of this research was to know how the using of journal dialogue and genre-based approach in writing hortatory text at the eleventh grade students of SMA Negeri 1 Beber and SMA Negeri 1 Jalaksana. This research was a content analysis study that consisted of three meetings. In doing the research, the writer involved 61 students of Class XI Social 3 and 4, one English teacher as the collaborator and the writer herself. In this research, there were two kinds of data. The first data were qualitative. To obtain the qualitative data, the writer conducted observation, interviews, and evaluating students’ writing tasks. The qualitative data were in the form of field notes, observation checklists result, interview transcripts, and students’ writing. Meanwhile, the quantitative data were presented in the score of the students’ writing task from students’ worksheet 2 in the third meeting. The result of this study shows two things. 1) The using of journal dialogue can improve students’ writing skills. Students’ writing problems can be reduced by applying journal dialogue. The feedback given by the writer facilitates the students to find and to correct their errors in the writing aspects, namely content, organisation, vocabulary, grammar and mechanics. In reference to the students’ writing scores, the students’ ability in those five aspects of writing improved after the journal dialogue strategy was given. It can be seen that the students’ mean value gain from the students’ worksheet 2 for class XI social 3 and 4 in the content aspect is 3.52; the organisation aspect is 3.87; then the vocabulary aspect is 3.57; then the grammar aspect is 2.9; and the mechanics aspect is 2.9. 2) The using of genre-based approach can be an efective method in improving student’s writing skill explicitly through the stages of BkoF, MoT, JcoT, and IcoT, and it created students have opportunities and time in writing, grow motivation to write English. So, it prepared students with targeted learning where they develop meaningful and communicative language skills through text, especially when the students write a hortatory text..Keyword: Journal Dialogue, Genre-Based Approach, Writing, Hortatory Exposition